MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK MELALUI PEMBELAJARAN BERBASIS MASALAH - yustin sriserang (UNM Journal of Biological Education, 2018)
This research is a classroom action research that to improve students activity and learning outcomes in class XI IPA 5 SMA Negeri 5 Makassar through the implementation of problem-based learning model. The subjects of this study were students of class XI IPA 5 in the second semester of the school year 2017/2018, the number of students 36. The research was conducted in two cycles. Data collected by used observation sheets, and cognitive test. Data were analyzed quantitatively and qualitatively. The results showed that there was improve student  activity and  learning outcomes from the first cycle to the second cycle. The conclusion of this research is the implementation of problem-based learning model can improve students activity and learning outcomes of students in class XI IPA 5 SMA Negeri 5 Makassar.